L’évolution du droit minier chilien (1874-1971) - Zunilda Carvajal-DelMar (Les Cahiers ALHIM)
From 1811 to 1976, four mining codes succeeded each other in Chile. This legal instability shows difficult it was for the legislator to abandon the colonial legal system and to adjust to the mining reality of the country. Yet, not all of the mining system was subject to changes: State’s prerogatives were not concerned with the reforms. The particular link between the State and the mines was long seen as belonging to the eminent domain. The 1971 constitutional reform compelled the authors to question this assessment.